Knowledge and practices of school adolescents in situation of obesity - Gudelia, Nájera-Gutiérrez; María Claudia, Morales-Rodríguez; Brenda, Resendiz-Maldonado; Rosa María Teresa , Tlalpan-Hernández (Seven Editora, 2023)
Introduction. The World Health Organization (WHO) defines adolescence to the stage which takes place between 10 and 19 years old, is one of the most complex stages and determinants of life, characterized by transformation from child to adult biological and psychosocial. From the anthropometric viewpoint, more than 20% of the total growth of height and up to 50% of adult bone mass is reached during adolescence, hence the importance of adequate nutritional intake through a varied and balanced diet. This context could be approached to make approximations to reality, knowing the knowledge and practices adolescent food from a qualitative paradigm. Objective: To describe the knowledge and practices of school adolescents in situation of obesity. Methodology: Descriptive, qualitative approach participant observation and in-depth interview technique was used. The interviews were conducted until theoretical saturation. The population was made up of seven students of basic level, with a diagnosis of obesity. For the analysis of the information analysis of thematic content is worked. Results: The analysis of speeches showed a category: knowledge (in) common adolescent and family contains two attributes: 1.1) the knowledge of adolescents regarding obesity and 1.2) the knowledge of the family with respect to adolescent obesity. Conclusions: The adolescent acquires this knowledge about obesity according to what the family transmitted it from generation to generation and these have not had impact, so does not become aware of the damage they can cause to their health and make healthy food and exercise care and practices to reduce this problem. DOI: https://doi.org/10.56238/Connexpemultidisdevolpfut-085